Extant Private Libraries of Oriental Manuscripts from Bosnia: Research Possibilities - Paić-Vukić, Tatjana (2012)
Most of the extant private libraries of Oriental (Arabic-script) manuscripts from Ottoman Bosnia are housed today in public archives and libraries in Bosnia and Herzegovina and abroad. Although they are rarely stored separately as distinct units, their original contents can be reconstructed to a certain point on the basis of registries and other documents comprising information on donors and sellers, and on the basis of marks of ownership that occur in the manuscripts. This reconstruction is facilitated today by indexes of former owners from the published catalogues. Since the manuscripts not infrequently bear various scattered inscriptions by people who owned them, such collections provide materials for a wide range of biographical, genealogical, microhistorical and cultural-historical researches. A broad research of this kind would be a fruitfull enterprise regardless to whether the owners were prominent persons or "ordinary" people of whom there is no mention in historical sources.
Projekt MZOS
ENG